2013
DOI: 10.1097/scs.0b013e3182670045
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Birth Months of Patients With Oral-Facial Clefts

Abstract: There is a possible seasonality in birth months and a difference between sexes of patients with oral-facial clefts in this native Chinese population. This approach could be useful to study the etiology and pathogenesis of oral-facial clefts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…Seasonal variation also occurs in the number of congenital anomalies, including orofacial clefts [ 7 9 ]. Seasonal variability in the occurrence of orofacial clefts has been reported, e.g., in Scotland [ 10 ], England [ 11 ], the United States [ 12 ], Zambia [ 13 ], Puerto Rico [ 14 ], Finland [ 15 ] and China [ 16 ]. In contrast, several studies have not confirmed the existence of seasonal variability of orofacial clefts, for example, in Georgia, USA [ 17 ], Colorado, USA [ 18 ], Northern Ireland [ 19 ] and Germany [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal variation also occurs in the number of congenital anomalies, including orofacial clefts [ 7 9 ]. Seasonal variability in the occurrence of orofacial clefts has been reported, e.g., in Scotland [ 10 ], England [ 11 ], the United States [ 12 ], Zambia [ 13 ], Puerto Rico [ 14 ], Finland [ 15 ] and China [ 16 ]. In contrast, several studies have not confirmed the existence of seasonal variability of orofacial clefts, for example, in Georgia, USA [ 17 ], Colorado, USA [ 18 ], Northern Ireland [ 19 ] and Germany [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…These data underline the fact that males and females must be assessed separately. Apart from Caton (2012) and Yin et al (2013), gender-related seasonal influences are described by some others (Owens et al, 1985;Fraser & Gwyn, 1998;Krost & Schubert, 2006;Peterka et al, 2018). Fraser and Gwyn (1998) found significant seasonal variation for males with cleft lip with or without cleft palate (CL+P) only.…”
Section: Gender Differencesmentioning
confidence: 99%
“…Summer months are characterized by higher outside temperatures and increased levels of sunlight, UV radiation, ozone concentrations, and agricultural pollutants (Krost & Schubert, 2006;Peterka et al, 2018). Some studies outside Europe, both in the northern and southern hemisphere, found significant increases in OFC development in seasons other than the summer (Charlton, 1966;Silberg et al, 1968;Amaratunga, 1989;De la Vega & Martinez, 2006;Elliott et al, 2008;Caton, 2012;Yin et al, 2013;Sofianos et al, 2018). Of these studies, those of Caton (2012) and Yin et al (2013) are most comprehensive and use control groups.…”
Section: Seasonal Variationmentioning
confidence: 99%
See 2 more Smart Citations